Impact of Enzymatic Degradation Treatment on Physicochemical Properties, Antioxidant Capacity, and Prebiotic Activity of Lilium Polysaccharides - Kaitao Peng; Yujie Zhang; Qi Zhang; Yunpu Wang; Yuhuan Liu; Xian Cui (Foods)
In order to overcome the bioavailability limitation of Lilium polysaccharide (LPS) caused by its high molecular weight and complex structure, two low-molecular-weight degraded polysaccharides, namely G-LPS(8) and G-LPS(16), were prepared through enzymatic degradation. The molecular weight of LPS was significantly reduced by enzymolysis, leading to increased exposure of internal functional groups and altering the molar ratio of its constituent monosaccharides. The results of antioxidant experiments showed that enzymatic hydrolysis had the potential to enhance the antioxidant performance of LPS. In vitro fermentation experiments revealed that LPS and its derivatives exerted different prebiotic effects on intestinal microbial communities. Specifically, LPS mainly inhibited the growth of harmful bacteria such as Fusobacterium, while G-LPS(8) and G-LPS(16) tended to promote the growth of beneficial bacteria like Megamonas, Bacteroides, and Parabacteroides. Metabolomic analysis revealed that LPSs with varying molecular weights exerted comparable promoting effects on multiple amino acid and carbohydrate metabolic pathways. Importantly, with the reduction in molecular weight, G-LPS(16) also particularly stimulated sphingolipid metabolism, nucleotide metabolism, as well as ascorbic acid and uronic acid metabolism, leading to the significant increase in specific metabolites such as sphingosine. Therefore, this study suggests that properly degraded LPS components have greater potential as a prebiotic for improving gut health.